2020
DOI: 10.1111/tid.13289
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologically documented infections after adult allogeneic hematopoietic cell transplantation: A 5‐year analysis within the Swiss Transplant Cohort study

Abstract: Background Infections are an important complication after allogeneic hematopoietic cell transplantation (allo‐HCT). The present study aimed at determining the landscape of infections occurring in a large cohort of allo‐HCT patients, as well as associated risk factors for infections and for one‐year non‐relapse mortality. Methods This is a retrospective cohort study using STCS and EBMT databases to assess the one‐year incidence rate of infection, as well as risk factors for infections and for one‐year non‐relap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…Sequences were considered clinically recognized viruses if they corresponded to a virus known to reactivate in/be frequently found among allo-HSCT recipients [2,4] or if the patient had a known chronic viral infection and clinically unrecognized viruses if not.…”
Section: Microbiological Methods Mngs and Sequence Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Sequences were considered clinically recognized viruses if they corresponded to a virus known to reactivate in/be frequently found among allo-HSCT recipients [2,4] or if the patient had a known chronic viral infection and clinically unrecognized viruses if not.…”
Section: Microbiological Methods Mngs and Sequence Analysismentioning
confidence: 99%
“…1 Division of Infectious Diseases, Geneva University Hospitals, 4 Rue Gabrielle-Perret-Gentil, 1211, 14 Geneva, Switzerland. 2 Laboratory of Virology, Division of Laboratory Medicine, Geneva University Hospitals, 4 Rue Gabrielle-Perret-Gentil, 1211, 14 Geneva, Switzerland. 3 University of Geneva Medical School, Geneva, Switzerland.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…From a general perspective, infectious complications are one of the most common complications after transplantation and are associated with significant morbidity and mortality (25,411,412). Among allo-HSCT recipients, a large Swiss multicenter study reported that viral infections were the most common infections after allo-HSCT, representing 74.2% of all infectious complications, followed by bacterial (22.4%) and fungal (3.5%) infections (411).…”
Section: Synthesis Critical Appraisal and Perspective Synthesismentioning
confidence: 99%
“…From a general perspective, infectious complications are one of the most common complications after transplantation and are associated with significant morbidity and mortality (25,411,412). Among allo-HSCT recipients, a large Swiss multicenter study reported that viral infections were the most common infections after allo-HSCT, representing 74.2% of all infectious complications, followed by bacterial (22.4%) and fungal (3.5%) infections (411). In this study, the underlying disease, donor type, CMV serological constellation, and GvHD were associated with the incidence rate of infections; furthermore, there was an increased risk for 1-year nonrelapse mortality associated with all pathogens (411).…”
Section: Synthesis Critical Appraisal and Perspective Synthesismentioning
confidence: 99%